STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA MELALUI EXPOSITORY LEARNING DI SMP NEGERI 2 TUREN KABUPATEN MALANG - Devi Devintya; Imam Safi’i; Adi Sudrajat (VICRATINA, 2022)
Discipline is one of the characters that must be taught to students because discipline will become the character of students until they grow up. The Covid-19 pandemic requires educational institutions to limit their learning activities and turn them into online learning and makes interaction between teachers and students limited so that there is a decrease in student learning discipline, therefore teachers must determine the right strategy so that learning can run well. This study aims to explain how the strategy of Islamic religious education teachers in improving student learning discipline through expository learning at SMP Negeri 2 Turen using a qualitative approach and the type of case study research. The conclusion of this study shows that the causes of students' lack of discipline in Islamic religious learning are due to online learning, misuse of mobile phones, and lack of awareness of discipline among school members. The strategy used by Islamic religious education teachers is the use of expository learning when learning in class and the existence of routine worship activities outside the classroom. The result of applying expository learning in Islamic religious education learning is that student learning discipline increases, learning is more effective and students understand the subject matter better